The hunters : two short novels - Messud, Claire, 1966- (New York : Harcourt, 2001)
In "A Simple Tale," Maria Poniatowski, a Ukrainian woman living in Canada, struggles with the widening gap between herself and her son Radek; and in "The Hunters," an American scholar living in a dreary London suburb becomes obsessed with the neighbors downstairs, particularly the caretaker for the elderly whose patients keep dying.
A simple tale -- The hunters.
Kirkus Review.
Pub Weekly.
Wilson's Fiction.
Adult
Keywords: American fiction